Omic analysis of the endangered Taxaceae species Pseudotaxus chienii revealed the differences in taxol biosynthesis pathway between Pseudotaxus and Taxus yunnanensis trees - Yu, Chunna (BMC Plant Biol, 2021)
BACKGROUND: Taxol is an efficient anticancer drug accumulated in Taxus species. Pseudotaxus chienii is an important member of Taxaceae, however, the level of six taxoids in P. chienii is largely unknown. RESULTS: High accumulation of 10-DAB, taxol, and 7-E-PTX suggested that P. chienii is a good taxol-yielding species for large-scale cultivation. By the omics approaches, a total of 3,387 metabolites and 61,146 unigenes were detected and annotated. Compared with a representative Taxus tree (Taxus yunnanensis), most of the differentially accumulated metabolites and differential expressed genes were assigned into 10 primary and secondary metabolism pathways. Comparative analyses revealed the variations in the precursors and intermediate products of taxol biosynthesis between P. chienii and T. yunnanensis. Taxusin-like metabolites highly accumulated in P. chienii, suggesting a wider value of P. chienii in pharmaceutical industry. CONCLUSIONS: In our study, the occurrence of taxoids in P. chienii was determined. The differential expression of key genes involved in the taxol biosynthesis pathway is the major cause of the differential accumulation of taxoids. Moreover, identification of a number of differentially expressed transcription factors provided more candidate regulators of taxol biosynthesis. Our study may help to reveal the differences between Pseudotaxus and Taxus trees, and promote resource utilization of the endangered and rarely studied P. chienii. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12870-021-02883-0.